2022
DOI: 10.1186/s12872-022-02877-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between atherogenic index of plasma and coronary artery disease in males of different ages: a retrospective study

Abstract: Background Atherogenic index of plasma (AIP) as a newly discovered blood lipid parameter was shown to be strongly correlated with coronary artery disease (CAD). However, the blood lipid levels changed with age, so we speculated that the correlation between AIP and CAD was also affected by age. Methods A retrospective study was performed on male patients with confirmed or suspected CAD who underwent coronary angiography (CAG) from July 2017 to Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Results from a large-scale nationwide population cohort study carried on in the Republic of Korea showed that AIP HRs for CVD risk were higher as compared to HRs of triglycerides and HDL cholesterol when those variables were applied in the regression model alone (42). Whereas, a study performed among 1,131 male patients with angiographically diagnosed CAD and without CAD found that the AIP predictive value for diagnosing CAD was not significantly different as compared with traditional blood lipids (43). Our results have shown a positive association between increasing values of AIP and risk of CVD mortality after adjustment to many confounders in men but not women responders.…”
Section: Discussionmentioning
confidence: 96%
“…Results from a large-scale nationwide population cohort study carried on in the Republic of Korea showed that AIP HRs for CVD risk were higher as compared to HRs of triglycerides and HDL cholesterol when those variables were applied in the regression model alone (42). Whereas, a study performed among 1,131 male patients with angiographically diagnosed CAD and without CAD found that the AIP predictive value for diagnosing CAD was not significantly different as compared with traditional blood lipids (43). Our results have shown a positive association between increasing values of AIP and risk of CVD mortality after adjustment to many confounders in men but not women responders.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, there was no significant association between AIP and CAD in elderly females aged ≥ 65 years [ 33 ]. Moreover, AIP could not predict the presence of CAD in elderly males who underwent coronary angiography [ 34 ]. A possible explanation to address this finding is that AIP level is increased in elderly population [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies the atherogenicity of blood serum is measured based on blood lipid parameters and age-related changes in atherogenicity index were demonstrated. In particular, it was shown that blood levels of total cholesterol, LDL, and triglyceride as well as plasma atherogenic index decreased with age in patients with ischemic heart disease (Hong et al, 2022). The other study of the association between plasma atherogenic index and risk of myocardial infarction demonstrated that a high plasma atherogenic index calculated as a ratio of blood triglycerides and HDL led to a greater risk of myocardial infarction in younger patients (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%